2019
DOI: 10.33314/jnhrc.v16i41.1631
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Pattern of Bacterial Pathogens Isolated from Infected Lesions

Abstract: Background: Wound infection with multidrug resistant bacteria along with risk factors is a major burden and challenge to the health care persons. This study focuses on antibiotic susceptibility pattern of bacterial isolates and risk factors of patients with infected wounds.Methods: This was a cross-sectional study conducted between November 2017 to June 2018 in Kathmandu University Hospital. Pus sample and wound swabs collected from patients during the study period were included. All microbiological processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…15 The current investigation found that out of 127 samples, 64 (50.39%) were culture positive, which is quite comparable to the results observed by Saleh et al (2008) in Bangladesh (48.19%), Gautam et al (2002) in northern India (37.7%), and Maharjan et al (2008) in Nepal (48.96%). 20,21,22 Comparatively, a 2018 study in Bangladesh found an isolation rate of 63.33 percent, which was significantly higher than the present study. 23 This high rate of isolation may be due to the prevalence of automated blood culture techniques.…”
Section: Figure-iii: Bacterial Identification By Automated Blood Cult...supporting
confidence: 83%
“…15 The current investigation found that out of 127 samples, 64 (50.39%) were culture positive, which is quite comparable to the results observed by Saleh et al (2008) in Bangladesh (48.19%), Gautam et al (2002) in northern India (37.7%), and Maharjan et al (2008) in Nepal (48.96%). 20,21,22 Comparatively, a 2018 study in Bangladesh found an isolation rate of 63.33 percent, which was significantly higher than the present study. 23 This high rate of isolation may be due to the prevalence of automated blood culture techniques.…”
Section: Figure-iii: Bacterial Identification By Automated Blood Cult...supporting
confidence: 83%
“…The most effective drugs against MRSA are linezolid and vancomycin with 100% sensitivity, followed by amikacin (79.3%). The results of the same study were shown by Sherchan and Gurung (2019) with an effective antibiotic for ESBL, namely imipenem (carbapenems) (93.8%) which also showed the highest sensitivity (97.14%) to meropenem (carbapenems). This small difference may be due to the geographically varying prevalence of ESBL-producing isolates.…”
Section: Discussionmentioning
confidence: 60%
“…Even if new antibiotics are developed, without behavior change, antibiotic resistance will continue to be a major threat [6]. In the meantime, information about the antibiotic spectrum of activity against existing MDR strains may help reduce the rate of emergence and spread of antimicrobial resistance [7].…”
Section: Introductionmentioning
confidence: 99%